Immigration Policy, International Talent and the Future of U.S. Higher Education: Potential and Existential Threats Analysis - Ahmed, Feroz (Journal of Humanities and Social Sciences Studies, 2026)
The U.S. has gained many benefits over the years through partnerships in higher education and immigration, including the recruitment of talent and international students who contribute to innovation and research within the system and the economy. The latest changes to immigration policies by the U.S. federal government pose a threat to this relationship. This research investigates the relationship between immigration policy and the sustainability of U.S. higher education, focusing on the academic years 2020 to 2025. The study reviews immigration policies, economy, immigration data, and research to ascertain the implications of changes in the U.S.’s immigration policy and the flow of international students into the U.S., resulting in a loss of 43 billion/yearly and a competitive disadvantage in the global economy. Findings indicate that international students at U.S. institutions are approximately 6% of total enrollments, and 57% of them study in fields like STEM that are critical to U.S. innovation. The study examined the impact of policy shifts, such as visa revocations, travel bans, and deportations, which would cause international enrollments in higher education to fall by 17% in the academic year that begins this fall of 2025. The research has policy implications for full-scale reforms by the U.S. federal government that provide trade-offs between national security concerns and strategic talent-retention priorities.